Formalizing Natural Languages with NooJ 2019 and Its Natural Language Processing Applications : 13th International Conference, NooJ 2019, Hammamet, Tunisia, June 7–9, 2019, Revised Selected Papers /: 13th International Conference, NooJ 2019, Hammamet, Tunisia, June 7–9, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available